Управління безпекою особистості як парадигма сталого розвитку гендерно-орієнтованого бюджетування - Ортіна, Ганна Володимирівна; Трусова, Наталя Вікторівна; Ortina, Hanna; Trusova, Natalia (Запоріжжя : 2023, 2023)
UA: В статті проведено комплексне дослідження теоретичних положень управління безпекою особистості як парадигми сталого розвитку гендерно-орієнтованого бюджетування в Україні, скрізь призму концептуального аспекту. Визначено, що складність системи управління безпекою особистості та рівності прав індивідуума в соціумі є тим джерелом потенціалу сталого розвитку суспільства, що дозволяє поступово вибудовувати гендерний підхід та впроваджувати його у сектор державного управління, приймати пріоритетні рішення на користь та в інтересах жінок, чоловіків з метою успішних взаємовідносин в середовищі їх існування. Обґрунтовано, що чим ближче концепція до своєї оригінальної концептуалізації за сукупністю загроз, тим більш складними стають і політика, і концепція управління безпекою особистості. Доведено необхідність розробки нової моделі безпечної політики управління особистістю через призму гендерно-орієнтованого бюджетування, вихідні положення якого розглядаються не як витрати на фінансування соціальної сфери, а як інвестиції в потенціал економічно активних людських ресурсів. Відповідність моделі бюджетної політики до вимог національної безпеки держави дозволяє розмежовувати повноваження в гендерно-орієнтовному бюджетуванні на предмет активізації жінок в соціальній сфері та їх місця на всіх рівням влади. EN: The article conducts a comprehensive study of the theoretical provisions of personal security management as a paradigm of sustainable development of gender-oriented budgeting in Ukraine, everywhere through the prism of the conceptual aspect. It is substantiated that the closer the concept is to its original conceptualization in terms of the set of threats, the more complex both the policy and the concept of personal security management become. It has been proven that the management of personal safety is formed by the combination of two elements – protection and empowerment of individuals. It was determined that for the European Union, the management of personal security is a narrative that includes the goals and methods of an extremely diverse system of external security policy, which has a presentational form of discussions about security to various audiences, both public and professional sectors. The essence andinterpretation of the concept of "gender" is determined, unlike a biological feature, it is a socio-role and cultural trait of the personality and behavior patterns of men and women to ensure gender equality at the national level, taking into account the gender relations that have developed in society for the development of the most effective mechanisms, elimination of gender stereotypes and prejudices, ensuring and confirming the successful development of the activities of state authorities, political parties, and civil organizations. The compliance of the budget policy model with the requirements of a socially secure state is delineated by the powers in gender-oriented budgeting on the subject of the activation of women in the social sphere and their place at all levels of power, as well as the systematization of legislative norms and requirements of international law and gender balance in the field of social sphere and budget policy, which is implemented within the framework of public administration.
Management of personal security as a paradigm of sustainable development of the gender-oriented budgeting
Keywords: особистість; гендер; гендерна рівність; безпека особистості; управління безпекою особистості; гендерно-орієнтовне бюджетування; personality; gender; gender equality; personal safety; personal safety management; gender-oriented budgeting